Problem Kosmologi Dalam Filsafat lbnu Rusyd - Mustofa, M. Lutfi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2002)
Philosophical discourse of universe creation was a phenomenon which characterized the dynamic views of Moslems scholars. This theme became an up to date topic as Moslems were faced with the exhaustive discussions to strengthen their beliefs on the existence of God and universe. In addition, this was also related to the great efforts made by the Moslems scholars to protect their concept on Tauhid and Aqeedah not to be contaminated by the thoughts aid concepts developed by non Moslem scholars. This writing aims at uncovering Ibn Rusyd philosophy on cosmology. lbnu Rusyd stated that universe was gradually created. Thus, the creation should be a process of changing one to another or change the potential into an actual creation. All these processes were done continuously in indefinite period.